Kajian Yuridis Penyelesaian Sengketa Medik di Indonesia - Supeno Supeno (Universitas Batanghari Jambi, 2019)
The higher level of education and welfare of the community will make the level of legal awareness of the community higher too, in the present context health care is not only seen as an ordinary relationship but has become a legal relationship between health workers and patients, in that relationship disputes can occur between the two sides parties, in fact many cases / medical disputes are directly processed criminally, Indonesian law has stipulated that if a case occurs then it can be resolved through administrative, civil and criminal law, the purpose of this study is to examine the main priorities of medical dispute resolution in case of suspected error and / or negligence committed by health workers. This paper is an idea and legal study that the author peels normatively. The results of the study indicate that if there is a suspicion of error and / or negligence made by a health worker must be checked first by an honorary assembly and sought as far as possible mediated.